Amniocentesis for the detection of congenital toxoplasmosis: results from the nationwide Austrian prenatal screening program. (February 2015) - Prusa, A.-R.; Kasper, D.C.; Pollak, A.; Olischar, M.; Gleiss, A.; Hayde, M.
Abstract: Prenatal diagnosis of congenital toxoplasmosis (CT) influences therapeutical management in pregnant women and their offspring. In Austria, a nationwide serological healthcare program to identify potential maternal toxoplasma infections during pregnancy exists. We assessed the clinical use of amniocentesis for toxoplasma-specific polymerase chain reaction (PCR) on amniotic fluid to detect CT. Data on serology, amniocentesis, PCR, complications, treatment, and paediatric clinical outcome were collected retrospectively among the birth cohort 1992–2008. There were 1386 women with amniocentesis, but only in 707 cases (51%) was acute maternal infection confirmed serologically. A high proportion (49%) of amniocenteses with negative PCR results in women with chronic infection or seronegativity were performed without clinical justification for the women or their foetuses. The positive and negative predictive values of PCR were 94.4% and 99.3%, respectively. Thirty-nine foetuses with CT, including four deaths, were reported. The five PCR-negative but infected infants were identified by the serological and clinical follow-up program. Thirty percent of amniocenteses were performed in the third trimester, and gestational age or treatment did not influence PCR sensitivity. Amniocentesis is indicated in women with acute maternal infection, and facilitated targeted therapies in pregnant women and their offspring. In women with late toxoplasma infection, negative amniotic fluid PCR made treatment of infants unnecessary. Serological and clinical follow-up of infants is important to confirm the infection status of the infant. Recommendations, based on our 17-year experience, to improve the current diagnostic strategies and to reduce unnecessary amniocentesis, are given.